The influence of task-based language teaching on Ideal L2 Self and Ought-to L2 self among Mandarin learners - Chua, Hui Wen; Lin, Chia Ying; Mohammad Affiq Kamarul Azlan, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The Malaysian Education Blueprint 2015-2025 (Higher Education) has highlighted the learning of third languages as one of its thrusts. However, little studies are done on the teaching and learning of Mandarin as a foreign language in the Malaysian context. This mixed-method study aimed at investigating the application of task-based language teaching (TBLT) in changing learners’ learning motivation, in terms of Ideal L2 Self and Ought-to L2 Self. This study involved 52 non-native Mandarin learners as participants. It also used a questionnaire and semi-structured interview for data collection. Findings show that overall, the non-native Mandarin learners' Ideal L2 Self and Ought-to L2 Self were always at a high level, and the application of TBLT in this study only slightly caused changes the learners' Ideal L2 Self and Ought-to L2 Self, which was their learning motivation. Besides, this study also discovered that there were two significant challenges of TBLT application, which interfered with the results of this study, which were time constraint and language knowledge requirement. This study implicates that in order to ensure the successful application of TBLT, course designing has to be thorough and detailed and takes into account the threats in the implementation of TBLT.